Glomerular Damage in Trichloroethylene-Sensitized Mice: Targeting Cathepsin L-Induced Hyperactive mTOR Signaling - Wang, Feng; Dai, Yuying; Huang, Meng; Zhang, Chenchen; Huang, Liping; Wang, Hui; Ye, Liangping; Wu, Qifeng; Zhang, Xuejun; Zhu, Qixing (Frontiers in Pharmacology, 2021)
Trichloroethylene (TCE) is a serious health hazard to the exposed workers, causing occupational medicamentosa-like dermatitis due to trichloroethylene (OMDT) with glomerular damage. Recent studies suggest that mTORC1 signaling activated in various glomerular disorders. A role of mTORC1 signaling in TCE-induced glomerular damage remains to be explored. To this end, six OMDT patients were enrolled and a mouse model of TCE sensitization was set up in the present study. The glomerular damage was assessed by levels of urine nephrin in OMDT patients and H&E staining with renal function test in mice. The ultrastructural change of podocyte was scanned under a transmission electron microscopy. The podocyte-related molecules including nephrin, α-actinin4, and integrin β1 were determined by immunofluorescence. The activation of mTORC1 signaling was confirmed by western blot. The glomerular apoptosis was examined by TUNEL test and western blotting. The expression and location of cathepsin L (CTSL) were assessed by RT-PCR and immunofluorescence. Our results showed that TCE sensitization caused damage to glomerular structural integrity evidenced by changes in several specific markers. TCE sensitization also increased the activation of mTORC1 signaling and this was accompanied by podocyte loss, hypertrophy and glomerular apoptosis. Importantly, we also found that over-expressed CTSL mainly located in podocyte and CTSL inhibition could partially block the activation of mTORC1 signaling. Thus, our findings suggested a novel mechanism whereby hyperactive mTOR signaling contributes to TCE sensitization-induced immune glomerular damage via CTSL activation.